An Energy Transfer System Design Using Wireless Power on Different Cross-Section Types - Nurmasyithah, Nurmasyithah; Hamdani, Hamdani; Solly Aryza (Sean Institute, 2024)
Wireless power transfer (WPT) technology has emerged as a transformative solu-tion for delivering electrical energy without the need for physical connections. This study investigates the design and performance optimization of an energy transfer system em-ploying WPT across different cross-section types of transmission coils, including circular, rectangular, and elliptical geometries. The objective is to analyze the impact of coil shape and configuration on power transfer efficiency, coupling strength, and electromagnetic field distribution. Using finite element analysis (FEA) and experimental validation, the study evaluates key parameters such as coil alignment, resonant frequency, and load var-iations under different cross-sectional designs. The results demonstrate that the geome-try of the coils significantly influences the system's power transfer efficiency, with circu-lar cross-sections exhibiting superior performance in terms of coupling factor and power density. However, rectangular and elliptical cross-sections offer distinct advantages in specific scenarios, such as space-constrained environments and non-uniform load distri-butions. This research provides a comprehensive framework for designing and optimiz-ing WPT systems tailored to diverse application requirements, including electric vehicles, medical devices, and consumer electronics. The findings contribute to advancing the ver-satility and efficiency of wireless energy transfer technologies, paving the way for more adaptable and reliable energy solutions in modern engineering applications.